2009
DOI: 10.5194/acp-9-3371-2009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stratospheric intrusions and intercontinental transport on ozone at Jungfraujoch in 2005: comparison and validation of two Lagrangian approaches

Abstract: Abstract. The particle dispersion model FLEXPART and the trajectory model LAGRANTO are Lagrangian models which are widely used to study synoptic-scale atmospheric air flows such as stratospheric intrusions (SI) and intercontinental transport (ICT). In this study, we focus on SI and ICT events particularly from the North American planetary boundary layer for the Jungfraujoch (JFJ) measurement site, Switzerland, in 2005. Two representative cases of SI and ICT are identified based on measurements recorded at Jung… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…An additional source of ozone in the troposphere is the downward transport from the stratosphere, where ozone is much more abundant (Levy et al, 1985). At high elevation sites such as the Jet Propulsion Laboratory Table Mountain Facility in southern California (TMF hereafter), the effect of the boundary layer is very small, and ozone variability is expected to be driven by transport processes from the stratosphere or horizontal transport within the troposphere (Cui et al, 2009;Naja et al, 2003;Trickl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An additional source of ozone in the troposphere is the downward transport from the stratosphere, where ozone is much more abundant (Levy et al, 1985). At high elevation sites such as the Jet Propulsion Laboratory Table Mountain Facility in southern California (TMF hereafter), the effect of the boundary layer is very small, and ozone variability is expected to be driven by transport processes from the stratosphere or horizontal transport within the troposphere (Cui et al, 2009;Naja et al, 2003;Trickl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high altitude of the measurement site (5079 m a.s.l. ), the values may appear low, if compared with the SI frequencies (ranging from 5% to 40%) inferred at high mountain stations located in Europe (with altitudes ranging from 2100 to 3800 m a.s.l., see Stohl et al, 2000;Cristofanelli et al, 2006;Cui et al, 2009;Trickl et al, 2010). It could indicate that the southern Himalayas is not among the world regions most affected by SI.…”
Section: Influence Of Stratospheric Intrusions On O 3 Concentrations mentioning
confidence: 99%
“…In particular, we decided to select as influenced by possible SI, the days for which at least one of the 14 back-trajectories ending in a vertical range extending up to 50 hPa from the NCO-P altitude showed PV>1.6 pvu, basing on the experience gained in the analysis of case studies of stratospheric intrusions at other high mountain stations (Cristofanelli et al, 2006;Cui et al, 2009) and at the NCO-P itself (Bonasoni et al, 2009). With the aim of minimize the fraction of wrong selections, the considered tracers were analysed in groups of two (or more) and only simultaneous identification have been retained for the analysis.…”
Section: Identification Of Stratospheric Intrusions At the Nco-pmentioning
confidence: 99%
“…Staudt et al, 2001;Liang et al, 2004;Yashiro et al, 2009;Zhang et al, 2006Zhang et al, , 2009Gilge et al, 2010), and therefore in this study they are used as indicators of the degree of influence of polluted air masses, in an attempt to determine whether this has an important effect on particle activation at the JFJ. Ozone at the JFJ may be influenced by stratospheric intrusions, but a modelling study (Cui et al, 2009) has suggested that this is the case for less than 20 % of the year, making such events relatively rare.…”
Section: Selection Of Predictor Variablesmentioning
confidence: 99%